2019
DOI: 10.1186/s13018-019-1208-8
|View full text |Cite
|
Sign up to set email alerts
|

Analyses of effect factors associated with the postoperative dissatisfaction of patients undergoing open-door laminoplasty for cervical OPLL: a retrospective cohort study

Abstract: Objectives This study aimed to investigate the effect factors associated with the postoperative dissatisfaction of patients undergoing open-door laminoplasty for cervical OPLL. Methods In this study, 194 patients, who underwent open-door laminoplasty for cervical OPLL from January 2009 to January 2016, were retrospectively reviewed. The Patient Satisfaction Index (PSI) was collected at discharge, 6 months, 1 year, and the last follow-up. According to the PSI, patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 30 publications
(24 reference statements)
0
6
0
Order By: Relevance
“…Kawaguchi et al 20 noted that poor recovery postoperatively was associated with kyphotic change of the cervical alignment and spinal cord signal intensity change on T2 weighted magnetic resonance imaging. Similarly, Liu et al 21 observed that patient dissatisfaction at long-term follow-up was associated with low improvement rate of JOA score and symptom recurrence. Therefore, several radiographic and clinical factors might be associated with surgical outcomes in c-OPLL patients.…”
Section: Discussionmentioning
confidence: 87%
“…Kawaguchi et al 20 noted that poor recovery postoperatively was associated with kyphotic change of the cervical alignment and spinal cord signal intensity change on T2 weighted magnetic resonance imaging. Similarly, Liu et al 21 observed that patient dissatisfaction at long-term follow-up was associated with low improvement rate of JOA score and symptom recurrence. Therefore, several radiographic and clinical factors might be associated with surgical outcomes in c-OPLL patients.…”
Section: Discussionmentioning
confidence: 87%
“…However, the posterior cervical spine also has its own defects, which can break down in the rear of the cervical muscle ligament complex, result in the destruction of the cervical vertebra rear anatomical structure and loss of stability, and cause post-operative stiffness, acid bilges, and pain in the neck, shoulder, and back, called axial symptoms (AS) [13,28,29]. Previous studies have shown that various factors may cause axial symptoms after surgery, including the choice of surgical method, the stability of posterior structures, the postoperative range of motion of the cervical spine, and the degree of soft tissue injury around the cervical spine.…”
Section: Discussionmentioning
confidence: 99%
“…Several items of NDI deal with the subjective perception of comfort. Though bias seems inevitable with NDI, postoperative cervical functional status of the patient does have a considerable impact on the patients’ life quality [18]. We think that NDI has a certain clinical significance and serves as an important measure for surgical outcomes.…”
Section: Discussionmentioning
confidence: 99%